Comparison of adaptive meshes for a singularly perturbed reaction–diffusion problem - Bugajev, Andrej; Čiegis, Raimondas (Mathematical Modelling and Analysis, 2012)
We consider a singular second-order boundary value problem. The differential problem is approximated by the Galerkin finite element scheme. The main goal is to compare the well known apriori Bakhvalov and Shishkin meshes with the adaptive mesh based on the aposteriori dual error estimators. Results of numerical experiments are presented.